Effects of family instability on child development and youth migration trends in Onitsha South local government area, Anambra State, Nigeria - Nneka, Chike Roseline; Bob-Eze, Nwamaka Nneka (Piramida Akademi, 2025)
Family stability is a cornerstone of societal development, providing children and youths with the emotional, social, and economic support needed to thrive. However, in Nigeria, the increasing prevalence of family instability has raised significant concerns about its implications on child development and youth migration trends. This study investigates the implications of family instability on child upbringing and its subsequent impact on youth migration in Nigeria. The study employed a descriptive survey design, gathering quantitative data via a 31-item, self-made questionnaire validated by three specialists. Conducted among 160 secondary school teachers in Onitsha South L.G.A., the survey focused on family instability, child upbringing, and youth migration. Internal consistency was assessed using Cronbach's alpha, and data were analyzed with SPSS version 22. Findings reveal diverse causes of family instability, including economic challenges, poor financial management, parental interferences, and extramarital affairs. The study explores the effects of family instability on children's behaviors, psychological well-being, and academic performance. Recommendations for mitigating these challenges encompass professional counseling, parental education, community support, and awareness campaigns. The study emphasizes the interconnectedness of behavioral, psychological, and health-related consequences, urging a comprehensive approach to address the complex issues associated with family instability and youth migration in Nigeria.